Fine‐needle aspiration cytology of juvenile granulosa cell tumour: A case report with summary of prior published cases. Issue 12 (9th August 2022) - Khatun, Farjana; Das, Anirban; Sengupta, Moumita; Chatterjee, Uttara; Sarkar, Ruchirendu
Abstract: Juvenile granulosa cell tumours (JGCT) are uncommon tumours of the ovary and can present diagnostic difficulty both on histology and cytology because of its rarity. Here we present the fine‐needle aspiration cytology (FNAC) findings of a 4 year‐old girl who came with a large abdominal mass and bleeding per vaginum. FNAC from the mass showed features suggestive of granulosa cell tumour (GCT) and which was later confirmed on histology to be of juvenile type. Only two cases of cytological findings of JGCT have been described earlier, both of which were recurrent cases and at metastatic sites. The main cytological feature in our case was presence of thick colloid like fluid containing apparent bubbles along with small clusters of uniform cells with eosinophilic cytoplasm and fine vacuolation. The presence of these secretions corresponding to the macrofollicles on histology has not been reported earlier